2014
DOI: 10.15346/hc.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Toward Complexity Measures for Systems Involving Human Computation

Abstract: This paper introduces the Human Oracle Model as a method for characterizing and quantifying the use of human processing power as part of an algorithmic process. The utility of this model is demonstrated through a comparative algorithmic analysis of several well-known human computation systems, as well as the definition of a preliminary characterization of the space of human computation under this model. Through this research, we hope to gain insight about the challenges unique to human computation and direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…AI has made constant efforts to model human intelligence; on the other hand, HC pursue solving tasks that are computationally challenging. These two research areas "hinge on the long-held belief that there exist problems that require human-level intelligence and reasoning to solve" [27]. When machine interpretations are not feasible or dependent on human interpretations then KM becomes the only source of knowledge creation.…”
Section: Human Computations In Citizen Crowds: a Knowledge Management...mentioning
confidence: 99%
“…AI has made constant efforts to model human intelligence; on the other hand, HC pursue solving tasks that are computationally challenging. These two research areas "hinge on the long-held belief that there exist problems that require human-level intelligence and reasoning to solve" [27]. When machine interpretations are not feasible or dependent on human interpretations then KM becomes the only source of knowledge creation.…”
Section: Human Computations In Citizen Crowds: a Knowledge Management...mentioning
confidence: 99%
“…Recently Sacha et al reviewed the role of visual analytics in machine learning, and outlined several open challenges [44]. Crouser et al suggested that the complexity of human computation can be measured [15]. Visual analytics can provide model developers with an effective means to explore data points in a high-dimensional space (e.g., [13,30]).…”
Section: Human-centric Classificationmentioning
confidence: 99%